Peran Satuan Sabhara Dalam Mencegah Tawuran Antar Pelajar Di Wilayah Polresta Bogor Kota Guna Terciptanya Kamtibmas - Prabowo, Bayu Aji (Indonesian Journal of Police Studies, 2020)
This research is backed by the case of a brawl between students in the Bogor area of the city that many injured victims until the death toll. Often we see in television media about the case of juvenile delinquency namely brawl, so in this study will discuss about the factors that cause the occurrence of the brawl between students and how the execution of the task of Sabhara Patrol Unit in the effort to prevent the occurrence of the brawl between students to create a kamtibmas in Bogor Kota.The research method that the author chose is qualitative research. In qualitative research prioritizes the quality of the data gained and remembers short and limited research time. In qualitative research, the authors dive directly into the field to meet with the speaker and dig the information needed. This is because the information needed is descriptive, which is to theoretically explain the steps taken by the Sabhara unit Bogor Kota in optimizing the prevention of the occurrence of the brawl between students.For five years backwards from 2016 to 2020, there have been 36 laughs in the area of Bogor city. The role of Sabhara's unit already has focus on people, places, material losses, and goods. Factors of the cause of the brawl are divided into two internal and external. And, for the execution of patrol tasks based on planning, organizing, implementation, and control.The suggestion of the whole problem is the strict rule of the school in relation to students ' laughs, both at the reception of new students and all students who have been in school. Another suggestion is to conduct patrol and socialization activities related to the student's brawl in order not to make room for students to make a brawl in the territory of Polresta Bogor Kota.